Contribution of urbanization to the increase of extreme heat events in an urban agglomeration in east China. Issue 13 (3rd July 2017) - Yang, Xuchao; Ruby Leung, L.; Zhao, Naizhuo; Zhao, Chun; Qian, Yun; Hu, Kejia; Liu, Xiaoping; Chen, Baode
Abstract: The urban agglomeration of Yangtze River Delta (YRD) is emblematic of China's rapid urbanization during the past decades. Based on homogenized daily maximum and minimum temperature data, the contributions of urbanization to trends of summer extreme temperature indices (ETIs) in YRD are evaluated. Dynamically classifying the observational stations into urban and rural, this study presents unexplored changes in temperature extremes during the past four decades in YRD and quantifies the amplification of the positive trends in ETIs by the urban heat island effect. Overall, urbanization contributes to more than one third of the increase of intensity of extreme heat events in the region, which is comparable to the contribution of greenhouse gases. Compared to rural stations, more notable shifts to the right in the probability distribution of temperature and ETIs are found in urban stations. The rapid urbanization in YRD has resulted in large increases in the risk of heat extremes. Key Points: The observational stations in Yangze River Delta are dynamically classified into urban and rural types to evaluate urbanization effects Urbanization contributes to more than one third of the increase of hot days, warm night, and heat wave intensity Urban stations show more notable shifts to the right in the probability distribution of extreme temperature indices